The Role of Organizational Culture in Mediating the Influence of Digital Leadership and Transformational Leadership on Indonesian National Police Performance - Harley H. Silalahi; Mutiara S. Panggabean; Justine Tanuwijaya (Jurnal Multidisiplin Madani, 2023)
This research was conducted to analyze the role of organizational culture in mediating the influence of digital leadership styles and transformational leadership on Indonesian National Police Performance. The population in this study were every  personnel at the Directorate of Narcotics Criminal Investigation of the National Police and the Directorate of Drug Investigation at the Regional Police. The samples used in this study were 250 personnel from the Directorate of Drug Crime, Bareskrim Indonesian National Police and the Directorate of Narcotics Research at the Regional Police. This study uses the Structural Equition Model (SEM) method with Partial Least Square (SEM-PLS) and uses smartPLS 3 software. The results of this study are that organizational culture can mediate the influence of digital leadership and transformational leadership on Indonesian National Police Performance